PETROGRAPHIC CHARACTERIZATION OF BASALTIC ROCKS FROM THE BREUEH VOLCANIC FORMATION, BREUEH ISLAND, INDONESIA - Akmal Muhni; Alfi Syahrin; Lia Fitria Rahmatillah; Dewi Sartika; Dina Gunarsih; Amsir Amsir; Dian Darisma (Indonesian Physical Review, 2026)
The Breueh Volcanic Formation on Breueh Island, Aceh Besar District, is part of the outer arc volcanic zone related to subduction between the Indo-Australian and Eurasian plates. In addition, the volcanic rocks exposed on Breueh Island provide important geological information for understanding the volcanic history, tectonic processes, and magmatic evolution in the outer arc region of Aceh.  This study aims to determine the rock classification using optical petrography, and to evaluate its possible relationship to the regional tectonic setting. Petrographic analysis was performed on three basaltic rock samples collected from outcrops in the east–southeast area of the formation. Thin sections were examined under a polarizing microscope at Geological Engineering Laboratory Syiah Kuala University, and modal mineral percentages were quantified using the point-counting method with JMicroVision software. The analyzed rocks display massive to amygdaloidal textures, with amygdales filled by zeolite and celadonite. Petrographic observations show that the rocks are dominated by plagioclase (40.17–43%), pyroxene (3.58–20.17%), and opaque minerals (1–2.92%) as major constituents, with minor alkali feldspar (<6.5%), minor quartz (<2.33%), and olivine (~0.5%). Based on the IUGS/Streckeisen classification, all samples are classified as basalt. The occurrence of zeolite and celadonite indicates low-temperature hydrothermal alteration. The dominance of mafic minerals is consistent with basaltic magma typical of subduction-related volcanic settings. Overall, the petrographic characteristics suggest that the basaltic rocks are consistent with magma generated in a subduction-related outer arc volcanic environment.